2018
DOI: 10.1152/ajplung.00031.2018
|View full text |Cite
|
Sign up to set email alerts
|

DPP4 inhibition by sitagliptin attenuates LPS-induced lung injury in mice

Abstract: Acute respiratory distress syndrome (ARDS) is a severe clinical condition marked by acute respiratory failure and dysregulated inflammation. Pulmonary vascular endothelial cells (PVEC) function as an important pro-inflammatory source in ARDS, suggesting that modulation of inflammatory events at the endothelial level may have therapeutic benefit. Dipeptidyl peptidase-4 (DPP4) inhibitors, widely used for the treatment of diabetes mellitus, have been reported to have possible anti-inflammatory effects. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 46 publications
2
79
1
Order By: Relevance
“…Using CD26/DPP4 inhibitors in a lung ischemia/reperfusion model, predominantly a significant improvement of gas exchange, a better preservation of parenchymal ultrastructure and reduced neutrophil infiltration were found [21]. Furthermore, application of an CD26/ DPP4 inhibitor decreased serum DPP4 activity, BAL protein concentration, cell number and pro-inflammatory cytokine levels, and reduced pathological histological findings of lung injury such as edema, neutrophil invasion and disruption of lung tissue in LPS challenged mice lungs [22]. Moreover, a reduced inflammation of lung parenchyma combined with a reduced airway specific recruitment of T-cells [23] and decreased expression of surfactant proteins was found in asthma induced CD26/DPP4 deficient (DPP4/CD26 − ) rats compared to CD26/DPP4 positive rats (wild types) [24].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Using CD26/DPP4 inhibitors in a lung ischemia/reperfusion model, predominantly a significant improvement of gas exchange, a better preservation of parenchymal ultrastructure and reduced neutrophil infiltration were found [21]. Furthermore, application of an CD26/ DPP4 inhibitor decreased serum DPP4 activity, BAL protein concentration, cell number and pro-inflammatory cytokine levels, and reduced pathological histological findings of lung injury such as edema, neutrophil invasion and disruption of lung tissue in LPS challenged mice lungs [22]. Moreover, a reduced inflammation of lung parenchyma combined with a reduced airway specific recruitment of T-cells [23] and decreased expression of surfactant proteins was found in asthma induced CD26/DPP4 deficient (DPP4/CD26 − ) rats compared to CD26/DPP4 positive rats (wild types) [24].…”
Section: Introductionmentioning
confidence: 93%
“…They found (1) a CD26 mediated costimulation of T-cells combined with production of the proinflammatory interleukin-2 (IL-2) [59], (2) a CD26 mediated co-stimulation of CD8 + T cells, which exert cytotoxic effects predominantly via TNF-α [18], (3) a DPP4 dependent cleavage of the chemokine substrate LD78ß into a very efficient monocyte attractant, enhancing lymphocyte and monocyte chemotactic activity [60], and (4) a CD26/DPP4inhibitor dependent increase of the anti-inflammatory peptide VIP (Vasointestinal peptide) in rats [61], diminishing inflammatory response [15,21]. Furthermore, using different CD26/DPP4 inhibitors signs of inflammation were reduced in different lung disease models [22,62,63]. Not at all, our group found a reduced inflammation in CD26/ DPP4 − rats [24].…”
Section: Cd26/dpp4 Dependent Differencesmentioning
confidence: 99%
“…DPP‐4 inhibitors may be of potential use for severe COVID‐19 by suppressing T cell proliferation and the production of pro‐inflammatory cytokines 22 . For example, Takeshi et al 23 showed that sitagliptin alleviated lung injury by inhibiting pro‐inflammatory cytokines IL‐1β, TNF‐α and IL‐6 in an experimental model of ARDS, which was also the main cause of SARS‐CoV‐2‐induced death. Ta et al 24 detected that alogliptin reduced Toll‐like receptor 4 (TLR4)‐mediated up‐regulation of IL‐6 and IL‐1β in diabetic ApoE −/− mice.…”
Section: The Function Of Dpp‐4 Inhibitors In Covid‐19mentioning
confidence: 99%
“…Other antihyperglycemic medications might have a protective role in ARDS. Metformin, peroxisome proliferator-activated receptor-␥ (PPAR-␥) agonists, glucagon-like peptide 1 (GLP-1) agonists, and dipeptidyl peptidase 4 (DPP4) inhibitors attenuated lung injury in murine models (13,21,38,39). Some of these medications might modulate ACE2 expression.…”
Section: Afif Nakhleh and Naim Shehadehmentioning
confidence: 99%